2008
DOI: 10.1159/000185719
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crofelemer in the Treatment of Diarrhea-Predominant Irritable Bowel Syndrome Patients

Abstract: Background: Crofelemer improves bowel function in several conditions characterized by states of prominent secretory diarrhea. Aim: This double-blind, randomized, placebo-controlled trial evaluated the effects of 3 dose levels of crofelemer in patients with diarrhea-predominant irritable bowel syndrome (D-IBS). Methods: Male and female patients were randomly assigned to receive crofelemer 125, 250 or 500 mg or placebo twice daily for 12 weeks. The primary efficacy measure was a responder for improvement in stoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…We did not investigate the possibility that crofelemer metabolites formed in the intestine might have additional cellular effects on enterocytes. The dual inhibition of CFTR and CaCC Cl Ϫ channels by crofelemer provides insights into the understanding of its therapeutic effects in the treatment of secretory diarrheal disorders of various etiologies (Holodniy et al, 1999;DiCesare et al, 2002;Mangel and Chaturvedi, 2008), which share the common feature of excessive Cl Ϫ secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not investigate the possibility that crofelemer metabolites formed in the intestine might have additional cellular effects on enterocytes. The dual inhibition of CFTR and CaCC Cl Ϫ channels by crofelemer provides insights into the understanding of its therapeutic effects in the treatment of secretory diarrheal disorders of various etiologies (Holodniy et al, 1999;DiCesare et al, 2002;Mangel and Chaturvedi, 2008), which share the common feature of excessive Cl Ϫ secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Additional pharmacological studies have shown that crofelemer reduced fluid secretion in cell culture and mouse models (Gabriel et al, 1999). Crofelemer is currently in clinical trials for the treatment of secretory diarrheas associated with acute infections including cholera, chronic diarrhea associated with HIV/AIDS, and diarrhea-predominant irritable bowel syndrome (Holodniy et al, 1999;DiCesare et al, 2002;Mangel and Chaturvedi, 2008). Here, we report that the antisecretory mechanism-of-action of crofelemer involves inhibition of both CFTR and CaCC Cl Ϫ channels at the luminal membrane of enterocytes.…”
mentioning
confidence: 82%
“…4 However, in a double-blind, randomized, placebo-controlled trial, crofelemer, a channel chloride blocker of both CFTR and the calcium-activated chloride channels, did not produce a benefit in stool consistency in diarrhea-predominant IBS patients. 5 Second, the possible secretion of colonic mucus…”
Section: Q1 Q2mentioning
confidence: 99%
“…These agents relieve pain and improve diarrhoea in patients with IBS-D [104,105]. Although large RCTs in un-subtyped IBS have not shown asimadoline to improve pain/discomfort as compared with placebo [105], patients with IBD-D experienced significant improvement in adequate relief of IBS pain (47 %) Crofelemer Regulates fluid secretion and water loss due to diarrhoea and normalizes chloride ion and water flow in the GI tract by inhibiting the cAMP-stimulated CFTR chloride ion channel and the CaCC in the luminal membrane Use of crofelemer was evaluated in a double-blind placebo-controlled RCT in 242 patients with IBS-D for 12 weeks [106]. The primary endpoint was a responder for improvement in stool consistency.…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Another treatment for IBS-D is the drug crofelemer, which has been shown to normalize chloride ion channel and water flow in the GI tract and therefore regulates fluid secretion and water loss by inhibiting ion channels in the luminal membrane [106]. However, crofelemer did not improve bowel frequency when compared with placebo, although an improvement in pain/discomfort was seen in females with IBS-D.…”
Section: Emerging Therapiesmentioning
confidence: 99%